Norwegian verb particles - Aa, Leiv Inge (Studies in Germanic linguistics (Amsterdam, Netherlands) ;, 2020)
"This book aims to explain the syntax and semantics of Norwegian verb particles. While particles have been claimed to be distributed optionally to the left (as LPrt) or right (as RPrt) of an associated DP in the linguistic literature, the dialectologically-oriented literature has shown for a long time that Norwegian particles are preferred as LPrt (indicated by a plus sign here): 'throw {+LPrt out} the dog {-RPrt out}'. While spatial particles can appear in both positions, non-spatial particles primarily appear to the left. A non-spatial LPrt construction triggers an atelic reading, and the RPrt counterpart identifies a result state. The book combines traditional dialectology with modern linguistic theories and includes much Norwegian data that has not been shed theoretical light on before: simplex and complex spatial and non-spatial constructions, phrasal particles, ground promotion, and unaccusatives. Several earlier theoretical accounts that have included an analysis of Norwegian particles, are reviewed in a separate chapter. Finally, a complex-predicate analysis is adopted for non-spatial particles, and a small clause analysis for spatial particles"--